The KfW/ZEW start-up Panel: design and research potential - Fryges, Helmut [Verfasser]; Gottschalk, Sandra [Verfasser]; Kohn, Karsten [Verfasser] (My University, 2010)
So far, there has been no data set which observes firm formations in Germany not only on a cross-sectional basis using one-time surveys, but continuously over a number of years. Therefore, the Centre for European Economic Research (ZEW), KfW Bankengruppe and Creditreform set up a panel study of newly founded firms in Germany: the KfW/ZEW Start-up Panel. In each wave of the KfW/ZEW Start-up Panel computer-aided telephone interviews (CATI) are conducted with about 6,000 newly founded firms. Three stratification criteria are applied in order to construct the sample of the panel: year of firm formation, sector, and whether or not the firm has been promoted by KfW Bankengruppe. In each year, a random sample of firms which have been founded within three years prior to the year of the survey is drawn. The start-up panel covers almost all industry sectors. Half of the firms included in the sample operate in a hightechnology industry. The first panel was conducted in spring 2008. This paper describes the design and the research potential of the KfW/ZEW Start-up Panel. (BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; T 3.4 Befragung; T 3 Forschungsmethoden; Unternehmensgründung; Wirtschaftszweig; Betriebsbefragung; Datengewinnung; Datenanalyse; Interview; Datenzugang; Quantitative Angaben; Bundesrepublik Deutschland